Technical and economical performance of parabolic through collector power plant (SEGS VI) - YOUSFI, ML; ZAARAOUI, Abdelkader; SAID, N (Congrès français de mécanique, 2011)
Concentrating solar power plants are an excellent alternative to conventional ones particularly in countries that lie in the Sun Belt. SEGS plants installed in California were the subject of several studies. In this work, we propose the study and simulation of the SEGS VI for its implementation in Algeria. A numerical model was developed using TRNSYS. Four sites were selected for simulation. The results have enabled us to calculate the price per kWh for selected sites. Based particularly on LEC lowest, we selected for the implementation of such a central site of Bechar.
Keywords: Solar thermal power plant; TRNSYS simulation; parabolic trough collector; Renewable energy; SEGS VI.